Controlled Position Navigation of Single Degree Magnetic Levitation - Dhiraj Basnet; Anusha Lamichhane; Amrit Panthi; Bipin Lamichhane; Mahammad Badrudoza; Ram Prasad Pandey (IAES Indonesia Section, 2019)
A permanent magnet is levitated following the electromagnetic suspension principle using the attractive magnetic force of a wire-wound electromagnet with a hall-effect sensor for position feedback. Taking the hall-effect voltage as an analog parameter and feedback signal to the micro-controller, the strength of the electromagnet is controlled by adjusting the current using the Pulse Width Modulation technique in order to levitate the permanent magnet. The stability of the levitated magnet is enhanced by the use of PID algorithm in the embedded system. Use of Laplace transform for simplification of differential equations and Taylor series for the linearization of system function supports the mathematical computation required for the levitation. Furthermore, by making the feedback signal from hall-effect sensor dependent only on the magnetic field of levitating magnet, an advancement in levitation phenomenon is achieved that aids the levitation with a greater flexibility of changing the position of the levitating magnet along the gravitational axis within a specified range.So the paper depicts about the